Translations In Times of Disruption : An Interdisciplinary Study in Transnational Contexts - Hook, David; Iglesias-Rogers, Graciela (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book throws light on the relevance and role played by translations and translators at times of serious discontinuity throughout history. Topics explored by scholars from different continents and disciplines include war, the disintegration of transnational polities, health disasters and revolutions - be they political, social, cultural and/or technological. Surprisingly little is known, for example, about the role that translated constitutions had in instigating and in shaping political crises at both a local and global level, and how these events had an effect on translations themselves. Similarly, the role that translations played as instruments for either building or undermining empires, and the extent to which interpreters could ease or hamper negotiations and foster new national identities has not been adequately acknowledged. This book addresses all these issues, among others, through twelve studies focused not just on texts but also on instances of verbal and non-verbal communications in a range of languages from around the world. This interdisciplinary work will engage scholars working in fields such as Translation Studies, History, Modern Languages, English, Law, Politics and Social Studies. David Hook is a Faculty Research Fellow at the Faculty of Medieval and Modern Languages of the University of Oxford, UK. A volume of essays in his honour was published by the Hispanic Seminary of Medieval Studies, New York, in November 2013. Graciela Iglesias-Rogers is Lecturer in Modern European and Global Hispanic History at the University of Winchester, UK, Associate Lecturer in Modern European and Latin American History at the University of Oxford, UK, and Fellow of the Higher Education Academy, UK. She is also a former Reuters Fellow with a long career as a leading foreign press correspondent.
Keywords: Linguistics.; World history.; Social history.; Literature -- Translations.; World politics.; Translation and interpretation.; elektronické knihy; electronic books